Do 5-6-Year-Old Girls Who Attend Gymnastics Achieve Better Motor Skills' Assessment Results Compared to those Who Do Not Attend Gymnastics - Florinta Čičirkaitė (Lithuanian Sports University, 2022)
Background. Children become less involved in various activities, and physical inactivity may negatively affect motor development. Motor skills are important for a child's development, so it is very important to know and track motor skills development. One of the methods for assessing motor skills is Bruininks - Oseretsky (BOT-2) test. The aim. to determine and compare the motor skills of 5-6-year-old girls who attend and do not attend gymnastics classes. Methods. 5-6 years girls participated in the study. We collected 15 who attended gymnastics classes and 15 age-matched controls. Gross motor skills were assessed using Bruininks-Oseretsky (BOT-2) test kit. Results. Bilateral coordination, balance, running speed and agility, upper-limb coordination, and strength of girls attending gymnastics classes were significantly higher (p <0.05) compared to girls not attending gymnastics. Conclusions. Attending gymnastics classes significantly improved motor skills of 5-6-year-old girls. Keywords: motor skills, preschool children, BOT-2.